Anatomical and Biochemical Changes Induced by Gluconacetobacter diazotrophicus Stand Up for Arabidopsis thaliana Seedlings From Ralstonia solanacearum Infection - Rodriguez, María V.; Tano, Josefina; Ansaldi, Nazarena; Carrau, Analía; Srebot, María S.; Ferreira, Virginia; Martínez, María L.; Cortadi, Adriana A.; Siri, María I.; Orellano, Elena G. (Frontiers in Plant Science, 2019)
Nowadays, fertilization and pest control are carried out using chemical compounds that contaminate soil and deteriorate human health. Plant growth promoting bacteria endophytes (PGPBEs), are a well-studied group of bacteria that offers benefits to the host plant, such as phytostimulation, biofertilization and protection against other microorganisms. The study of Gluconacetobacter diazotrophicus –which belongs to PGPBEs- aids the development of alternative strategies of an integrated approach for crop management practices. Ralstonia solanacearum is responsible for bacterial wilt disease. This phytopathogen is of great interest worldwide due to the enormous economic losses it causes. In this study the action of G. diazotrophicus as a growth promoting bacterium in Arabidopsis thaliana seedlings is analyzed, evaluating the antagonistic mechanisms of this beneficial endophytic bacterium during biotic stress produced by R. solanacearum. Effective colonization of G. diazotrophicus was determined through bacterial counting assays, evaluation of anatomical and growth parameters and pigments quantification. Biocontrol assays were carried out with R. pseudosolanacearum GMI1000 model strain and R. solanacearum A21 a recently isolated strain. Inoculation of A. thaliana (Col 0) with G. diazotrophicus Pal 5 triggers a set of biochemical and structural changes in roots, stems and leaves of seedlings. Discrete callose deposits as papillae were observed at specific sites of root hairs, trichomes and leaf tissue. Upon R. pseudosolanacearum GMI1000 infection, endophyte-treated plants demonstrated being induced for defense through an augmented callose deposition at root hairs and leaves compared with the non-endophyte-treated controls. The endophytic bacterium appears to be able to prime callose response. Roots and stems cross sections showed that integrity of all tissues was preserved in endophyte-treated plants infected with R. solanacearum A21. The mechanisms of resistance elicited by the plant after inoculation with the endophyte would be greater lignification and sclerosis tissues and reinforcement of the cell wall through the deposition of callose. As a consequence of this priming in plant defense response, viable phytopathogenic bacteria counting was considerably fewer in edophyte-inoculated plants than in not-inoculated controls. Our results indicate that G. diazotrophicus colonizes A. thaliana plants performing a protective role against the phytopathogenic bacterium R. solanacearum promoting the activation of plant defense system.